Eksistensi Jasa Transportasi Konvensional Milik Masyarakat Lokal pada Era Revolusi Industri 4.0 di Kelurahan Ubud, Bali - Situmorang, Fransisco; Anggi Hasian Silaban, Agnes; Rohmi, Ziyadatur; Suryawan, Ida Bagus (JURNAL DESTINASI PARIWISATA; Vol 8 No 1 (2020): VOL 8, NO 1 (2020): (JANUARY-JUNE) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2020.v08.i01.p19, 2020)
The presence of online transportation services in Ubud Village is considered a threat to the existence of conventional transportation services. Far-reaching price differences trigger conflict. This study aims to analyze the existence of conventional transportation services in the Ubud Village in the era of the industrial revolution 4.0. This study uses qualitative and quantitative data with primary and secondary data sources. Data obtained through the study of literature, observation, interviews, documentation, and questionnaires. The techniques for determining informants and determining the samples used are purposive sampling and incidental sampling. This research uses descriptive-qualitative analysis techniques and the Importance of Performance Analysis. The results showed that conventional transportation services still existed in the era of industrial revolution 4.0 due to an organization formed under the auspices of the Desa Adat which prohibits the operation of online transportation services. This research is expected to be a reference for the Bali Government and the Regency of Gianyar Government in compiling a policy regulation governing tourism transportation services in the Ubud Village. Keywords: Revolution 4.0, Existence, Transportation Service